Safety in petroleum industries - Ghosh, D. (Dhananjoy) (Boca Raton : CRC Press, 2021)
"Safety in Petroleum Industries covers pertinent safety aspects and precautions to be taken for design, operation, maintenance, inspection and project constructions for petroleum industries, with an emphasis on petroleum refineries"--
OCLC-licensed vendor bibliographic record.
Keywords: Petroleum -- Refining -- Safety measures; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Industrial Health & Safety; TECHNOLOGY / Material Science